DIVERSITY OF ARTHROPODS ON COCOA PLANTATION IN THREE STRATA OF SHADE TREE - Toana, Moh. Hibban; Mudjiono, Gatot; Karindah, Sri; Abadi, Abdul Latief (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2014)
The Research was aimed to identifythe diversity of arthropods in Cocoa plantation inthree strataof shade tree. Research was conducted in Rahmat village, the sub-district of Palolo, District of Sigi, the Province of Central Sulawesi, Indonesia from December 2012 to June 2013.Berlese funnel, Pitfall, Malaise and Light trap were used to collect arthropod samples. There were five indices such as species richness (R), species evenness (E), species diversity (H`and D), and species similarity (Iss) to analyze the diversity of arthropods in cocoa plantations. The result showed that species richness (R) of arthropods under the two strata of shade tree, species evenness (E) and both of species diversity indices, Shannon (H`) & Simpson (D) was the highest, with value of 18,216, 0.839, 4.383, and 0.833 respectively. In addition, percentage of species similarity (Iss) was the highest under two strata of shade tree with value 72.297%.Keywords: arthropods, cocoa, species diversity, two strata of shadetree